PENGARUH MEDIA DIGITAL WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR MATERI KEKAYAAN BUDAYA INDONESIA PADA SISWA KELAS IV SDN BANTARKEMANG 6 BOGOR - Nurharizah, Siti; Irvan Permana; Elly Sukmanasa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using Wordwall digital media to improve student learning outcomes on the material of Indonesia's cultural wealth using a quasi-experimental method with a two-group design. The population in this study were IVA and IVB grade students of SDN Bantarkemang 6 Bogor. Each class IVA and IV consists of 25 students. The research sample used the Total Sampling technique, namely using the entire existing population. Before conducting research, testing was carried out first using validity, reliability, differentiability, and difficulty level tests. The next stage both sample class groups will be given a pretest (initial test), then given treatment using digital Wordwall media (experimental class) and without using digital Wordwall media (control class) after that given a posttest (final test). Based on the results of the normality test, the significance results obtained were 0.144 in the experimental class and 0.110 in the control class where both data were normally distributed, then the homogeneity test obtained a significance result of 1.07 and in the hypothesis test obtained t_count of 6.4348 greater than t_table of 2.01063, indicating H_0 (null hypothesis) is rejected and H_a (alternative hypothesis) is accepted. it can be concluded that the use of Wordwall digital media has an effect on improving learning outcomes on the material of Indonesia's cultural wealth in grade IV students of SDN Bantarkemang 6 Bogor.